Recreating Hamlet: creativity of Vishal Bhardwaj in Haider - Kowsar, K. S. Shahanaaz; Mukherjee, Sangeeta (Creativity Studies, 2021)
William Shakespeare’s plays are universal in human character, which have raised him to be the exemplar in film industry. Shakespeare’s works stand to the test of time due to their intrinsic quality of life-likeness as Arthur Koestler comments that life-likeness is regarded as the supreme criterion of art. Shakespeare’s works and films project the reality of human life. The universality of his works has motivated the film producers to adapt Shakespeare extensively in their films in different regions, nations and contexts. The adaptation of the literary text into filmic interface involves major creative restructuring between the original text and the filmic medium. The restructuring of the adaptation involves shift in the medium, genre, context and culture to suit the differences in area and medium. The director of a film needs to be highly creative to adapt a literary text to make a film. Vishal Bhardwaj is one such contemporary prolific film makers who have successfully adapted Shakespearean plays like Othello, Macbeth and Hamlet into Indian cinema. The research article tries to portray the creativity of a director to recreate a new film out of an existing text (filmic adaptation). The article analyses the concept of conceptual blending creativity process and bricolage in highlighting the creativity of Bhardwaj in adapting Hamlet and localizing it in Indian cinema as Haider (2014).